Effect of ZnO on the physical properties and optical band gap of soda lime silicate glass - Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Ab. Aziz, Sidek; Zakaria, Azmi; Mohd Ghazali, Mohd Sabri (MDPI, 2012)
This manuscript reports on the physical properties and optical band gap of five samples of soda lime silicate (SLS) glass combined with zinc oxide (ZnO) that were prepared by a melting and quenching process. To understand the role of ZnO in this glass structure, the density, molar volume and optical band gaps were investigated. The density and absorption spectra in the Ultra-Violet-Visible (UV-Visible) region were recorded at room temperature. The results show that the densities of the glass samples increased as the ZnO weight percentage increased. The molar volume of the glasses shows the same trend as the density: the molar volume increased as the ZnO content increased. The optical band gaps were calculated from the absorption edge, and it was found that the optical band gap decreased from 3.20 to 2.32 eV as the ZnO concentration increased.